Analysis of Barriers that Affect the Success of the “Zero Waste North Lombok” Program - Suci, Dewinda Prameta; Rakhmatulloh, Anita Ratnasari (Universitas Ibn Khaldun Bogor, 2024)
Waste management is a cross-cutting issue that is closely related to various global challenges. At the local government level, waste management services carried out demonstrate the sustainability of a city so that local governments are responsible for finding affordable waste management solutions with the least impact on the environment. North Lombok Regency has a waste management problem that results in the realization of its handling not reaching the target. To overcome the waste management problem, the local government initiated a priority development program